Potential Neurodevelopmental Effects of Pediatric Intensive Care Sedation and Analgesia: Repetitive Benzodiazepine and Opioid Exposure Alters Expression of Glial and Synaptic Proteins in Juvenile Rats. (April 2020) - Iqbal O'Meara, Alia Marie; Miller Ferguson, Nikki; Zven, Sidney E.; Karam, Oliver L.; Meyer, Logan C.; Bigbee, John W.; Sato-Bigbee, Carmen
Abstract : Objectives: Sedatives are suspected contributors to neurologic dysfunction in PICU patients, to whom they are administered during sensitive neurodevelopment. Relevant preclinical modeling has largely used comparatively brief anesthesia in infant age-approximate animals, with insufficient study of repetitive combined drug administration during childhood. We hypothesized that childhood neurodevelopment is selectively vulnerable to repeated treatment with benzodiazepine and opioid. We report a preclinical model of combined midazolam and morphine in early childhood age-approximate rats. Design: Animal model. Setting: Basic science laboratory. Subjects: Male and female Long-Evans rats. Interventions: Injections of morphine + midazolam were administered twice daily from postnatal days 18–22, tapering on postnatal days 23 and 24. Control groups included saline, morphine, or midazolam. To screen for acute neurodevelopmental effects, brain homogenates were analyzed by western blot for synaptophysin, drebrin, glial fibrillary acidic protein, S100 calcium-binding protein B, ionized calcium-binding adaptor molecule 1, and myelin basic proteins. Data analysis used Kruskal-Wallis with Dunn posttest, with a p value of less than 0.05 significance. Measurements and Main Results: Morphine + midazolam and morphine animals gained less weight than saline or midazolam ( p ⩽ 0.01). Compared with saline, morphine + midazolam expressed significantly higher drebrin levels ( p = 0.01), with numerically but not statistically decreased glial fibrillary acidic protein. Similarly, morphine animals exhibited less glial fibrillary acidic protein and more S100 calcium-binding protein B and synaptophysin. Midazolam animals expressed significantly more S100 calcium-binding protein B ( p < 0.001) and 17–18.5 kDa myelin basic protein splicing isoform ( p = 0.01), with numerically increased synaptophysin, ionized calcium-binding adaptor molecule 1, and 21.5 kDa myelin basic protein, and decreased glial fibrillary acidic protein. Conclusions: Analysis of brain tissue in this novel rodent model of repetitive morphine and midazolam administration showed effects on synaptic, astrocytic, microglial, and myelin proteins. These findings warrant further investigation because they may have implications for critically ill children requiring sedation and analgesia.